How is The Volatility of Jakarta Islamic Index Stocks? - Erna Listyaningsih; Chandrasekhar Krishnamurti (Fakultas Ekonomi dan Bisnis Universitas Padjadjaran, 2016)
The Jakarta Islamic Index (JII) is the Islamic Index in Indonesia which is based on Sharia compliance, changes in market capitalisation and liquidity. This objective of the present study is to measure volatility of JII stocksand compare it with non-JII during 2005-2012 by using ARCH and GARCH models.The previous studies just comparing JII with other indices, a valid conclusion cannot be drawn as most of stocks belonging to JII are also included in the other indices. Therefore in this study we split stocks listed in Indonesian stock exchange into two periods: 2005-2007 which consists of two groups: JII and Non-JII and 2008-2012 which consists of three groups: JII, Sharia and Non-Sharia based on industry sector in order to investigate which one has the lowest volatility. This study uses two proxies of liquidity for each period namely: turnover and spread due to we use CAPM extended Fama and French and also augmented liquidity to calculate excess return.In the period of 2008-2012 found that there is GARCH (1,0) in which ARCH influences the volatility of return. Additionally, dummy-JII and dummy-Sharia influence negative significantly toward volatility of return as well. This finding alsorevealed that JII stocks have lower volatility compared to non-JII in which JII has the lowest leverage compared to Sharia and Non-Sharia. Therefore this result is consistent with the theory in which JII stocks has the lowest volatility due to their characteristic which is Sharia compliance, high market capitalization and high liquidity.